Pengaruh Faktor Riwayat Lahir dan Sosial Ekonomi terhadap Gizi Lebih pada Remaja - Pasaribu, Elita Oktorina; Martianto, Drajat; Dwiriani, Cesilia Meti (Media Kesehatan Masyarakat Indonesia, 2019)
Obesity is a major problem in the world, especially in adolescents whose prevalence increase and obesity in adolescents are multi-factorial desease. Birth history and socio-economic factors that influence obesity. The purpose of this study was to identify birth history and socio-economic factors for over nutrition in adolescents. The design of this study is a cohort study using secondary data from the Indonesian Family Life Surveys (IFLS) and carried out from December 2017 - August 2018. The study involved 426 adolescents aged 15-17 years. The statistical analysis used is Structural Equation Modeling (SEM). The direct effect on birth weight was gestational age (OR 7.7) (p <0.05). The direct effect of adolescent nutritional status was found in father’s education (p <0.05) and maternal BMI (p <0.05) had a significant effect, while maternal education (p> 0.05), income / capita / month (p> 0.05 ), and the living area (p> 0.05) did not find significant results for over nutrition in adolescents. Adolescents who have highly educated fathers and overweight or obese mothers are risk factor for adolescents to become over nutrition.